TINDAKAN SOSIAL TERHADAP PENOLAKAN POLIGAMI DALAM AKUN INSTAGRAM - Alfiyah Faizatul Arif (Institut Keislaman Abdullah Faqih Gresik, 2020)
Abstract: The issue of polygamy is widely echoed in online media. Not a few online media users are preaching the ability of polygamy. However, there are also online media users who refuse the reverberation of existing polygamy practices, as practiced by the @Indonesiatanpapoligami account in Instagram. Increasingly the number of followers continues to increase drastically making researchers want to examine more deeply how the account @indonesiatanpapoligami echoes the rejection of polygamy in his Instagram account. This research will analyze the rejection with a sociological approach. The approach used is a quali-tative approach. Based on the results of research that there are motives and goals of the ITAMI actors in rejection of polygamy, namely: First, seen based on the type of traditional action. Second, based on affective action. Third, instrumental rationales. Fourth, that what is done by ITAMI is part of an effort to sensitize the perpetrators of polygamy and spread the value of the original content of the existence of polygamy.Keywords: Polygamy, Social Action, Instagram